Glimpses of hope : the rise of industrial labor at the urban margins of Nepal - Hoffmann, Michael, 1958- (Berghahn Books, 2023)
"Over the last decade, Nepal has witnessed significant urban growth and an expanding urban middle class. Glimpses of Hope tells the story of the people who enable some of the middle-class consumer practices in urban Nepal. The book focuses on workers in areas such as modern food-processing, water-bottling, housebuilding, and sand-mining industries and explores how workers see such forms of work, where union organization can help, and how work opportunities emerge along lines of gender and ethnicity. Although global labor relations have been mostly in decline for decades, this ethnography offers insights and glimpses of hope in terms of labor dynamics and the opportunities various jobs may afford"-- Provided by publisher.
Keywords: Working class -- Nepal -- Social conditions.; Labor -- Nepal.; Urbanization -- Nepal.; City and town life -- Nepal.; Nepal -- Social conditions.; Travailleurs -- Népal -- Conditions sociales.; Travail -- Népal.; Urbanisation -- Népal.; Vie urbaine -- Népal.; SOCIAL SCIENCE / Anthropology / Cultural & Social.; City and town life; Labor; Social conditions; Urbanization; Working class -- Social conditions; Nepal; Electronic books.